The first steps in developing a number sense screening test for young primary school children - Katja Depolli Steiner; Cirila Peklaj; Anja Podlesek (Psihološka Obzorja)
Number sense refers to a set of numerical processing skills that develop before entering primary school and evolve with age and experience. Research has shown the importance of these skills for mathematical achievement. Therefore, early identification of students who have difficulty in numerical processing is the key to early intervention to reduce these deficits. This study’s purpose was to design a group-administered pencil-and-paper instrument measuring numerical magnitude estimation and numerical magnitude comparison that can be used in the first three grades of primary school as a quick screening tool for number sense deficits. Three quick and easy-to-use tasks measuring non-symbolic and symbolic number sense (the number line estimation task, the area comparison task, the number comparison task) were developed and administered to a group of 316 students in the first three grades of Slovenian primary schools. The results show that these tests provide a good basis for further development of a screening test.